Integrated Transcriptome Analysis of Human Visceral Adipocytes Unravels Dysregulated microRNA-Long Non-coding RNA-mRNA Networks in Obesity and Colorectal Cancer - Tait, Sabrina; Baldassarre, Antonella; Masotti, Andrea; Calura, Enrica; Martini, Paolo; Varì, Rosaria; Scazzocchio, Beatrice; Gessani, Sandra; Del Cornò, Manuela (Frontiers in Oncology, 2020)
Obesity, and the obesity-associated inflammation, represents a major risk factor for the development of chronic diseases, including colorectal cancer (CRC). Dysfunctional visceral adipose tissue (AT) is now recognized as key player in obesity-associated morbidities, although the biological processes underpinning the increased CRC risk in obese subjects are still a matter of debate. Recent findings have pointed to specific alterations in the expression pattern of non coding RNAs (ncRNAs), such as microRNAs (miRNAs) and long non coding RNAs (lncRNAs), as mechanisms underlying dysfunctional adipocyte phenotype in obesity. Nevertheless, the regulatory networks and interrelated processes relevant for adipocyte functions, that may contribute to a tumor- promoting microenvironment, are poorly known yet. To this end, based on RNA sequencing data, we identified lncRNAs and miRNAs, which are aberrantly expressed in visceral adipocytes from obese and CRC subjects, as compared to healthy lean control, and validated a panel of modulated ncRNAs by real-time qPCR. Furthermore, by combining the differentially expressed lncRNA and miRNA profiles with the transcriptome analysis dataset of adipocytes from lean and obese subjects affected or not by CRC, lncRNA–miRNA–mRNA adipocyte networks were defined for obese and CRC subjects. This analysis highlighted several ncRNAs modulation that are common to both obesity and CRC or unique of each disorder. Functional enrichment analysis of network-related mRNA targets, revealed dysregulated pathways associated with metabolic processes, lipid and energy metabolism, inflammation, and cancer. Moreover, adipocytes from obese subjects affected by CRC exhibited a higher complexity, in terms of number of genes, lncRNAs, miRNAs and biological processes found to be dysregulated, providing evidence that the transcriptional and post-transcriptional program of adipocytes from CRC patients is deeply affected by obesity. Overall, this study adds further evidence for a central role of visceral adipocyte dysfunctions in the obesity–cancer relationship.